2014
DOI: 10.1177/0022034514535604
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences of Tooth Loss and Obesity on Systemic Markers of Inflammation

Abstract: Sex-specific differences in the incidence of periodontitis and tooth loss may be related to different phenotypes of obesity and their associations with low-grade inflammation. The aim of this study was to evaluate associations of adiposity and lowgrade inflammation with tooth loss in men and women. Follow-up data of 2,714 participants from the cohort of Study of Health in Pomerania were analyzed for anthropometric measures, periodontitis, tooth loss, C-reactive protein (CRP), and interleukin 6. Regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
4
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 33 publications
(41 reference statements)
2
40
4
5
Order By: Relevance
“…However, the relatively lower hsCRP in the present study compared to other studies might have contributed. For instance, 26.6% of present study participants had hsCRP >2 mg/L compared to 32.2% in the study population of Meisel et al, 20 whereas a respective 2.6% and 18.3% of participants had hsCRP >3 mg/L and >10 mg/L compared to 2.9% and 19.5% in the study of Linden et al 11 …”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…However, the relatively lower hsCRP in the present study compared to other studies might have contributed. For instance, 26.6% of present study participants had hsCRP >2 mg/L compared to 32.2% in the study population of Meisel et al, 20 whereas a respective 2.6% and 18.3% of participants had hsCRP >3 mg/L and >10 mg/L compared to 2.9% and 19.5% in the study of Linden et al 11 …”
Section: Discussioncontrasting
confidence: 53%
“…Comparing those who have lost all their natural teeth to those with teeth, one study 18 showed significantly higher hsCRP among edentulous individuals, but another study 19 showed no difference. On the other hand, there is an indication that elevation of hsCRP might precede tooth loss, specifically in men, thus a dependent association between number of teeth and hsCRP is no longer seen cross‐sectionally 20 . Furthermore, risk factors for tooth loss are multifactorial and complex, 21 and some of these risk factors are also determinants of hsCRP concentrations 22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that handgrip strength is significantly associated with inflammatory markers including C‐reactive protein (CRP) and fibrinogen. Tooth loss is associated with elevated CRP . These limitations should be addressed in longitudinal study.…”
Section: Discussionmentioning
confidence: 97%
“…, Meisel et al. ). Naturally, the severity of such consequences of the oral inflammation increases with the ageing process.…”
mentioning
confidence: 98%